Protection of window glass from acoustic leakage - Lych, Sergij; Rakobovchuk, Volodymyr (Видавництво Львівської політехніки, 2013)
In a survey was presented an analysis of the most common glass samples on the Ukrainian market on their protection level against leakage of acoustic information. The glass samples were studied by means of roentgen analysis, and the impact of elemental composition of glass according to a laser beam reflection factor was defined.
Keywords: acoustic leakage; laser microphone; glass; analyzer; acoustic information